(De)constructing Politeia: Reflections on Citizenship and the Bestowal of Privileges upon Foreigners in Hellenistic Democracies *. Issue 3 (September 2014) - Müller, Christel; Gharibian, Arby
Abstracts: This article revisits the notion of citizenship ( politeia ) in the ancient Greek world, challenging the traditional conception, based principally on the works of Aristotle, that defines citizenship in terms of political participation. It considers the numerous decrees issued during the Hellenistic period bestowing legal privileges upon foreign benefactors (such as the right to own property, to trade, to enter into a legal marriage, to be exempted from certain taxes, and so on). If the Classical period's tripartite division of status (citizens, resident aliens, and slaves) remained valid during the Hellenistic period and provided the "infrastructure" of civic societies, the system of privileges established by cities to honor deserving foreigners created a "concatenation" of different positions, which, without calling the hierarchy of legal statuses into question, introduced social fluidity into an interconnected world that was far removed from the Platonic and Aristotelian ideals of the autarchic city.